ANALISIS PENGARUH DEBIT AIR TERHADAP UNJUK KERJA PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO TURBIN ULIR SKALA LABORATORIUM - MUHAMMAD FATHUR RAHMAN (LPPM Politeknik LP3I Medan, 2022)
The Screw Turbine MicroHydro Power Plant is a small-scale power plant that produces < 200 kW of power, which utilizes the power (flow) of water as a source of energy production. MHP is a renewable energy source and deserves to be called clean energy because it is environmentally friendly. In terms of technology, MHP was chosen because of its simple construction and easy operation. The screw turbine can be operated in remote settlements that do not have electricity by placing it in a river with medium or large discharge to produce electrical energy. This research was carried out based on the previous reference, where the screw turbine which was carried out during this study had a size with a shaft length of 870 mm, an outer diameter of 350 mm, a pitch of 290 mm with 2 blades (screw) with a 35° Treaded turbin tilt angle. The screw turbine in this study produced the highest generator power of 38.4 VDC at a water discharge of 0.0205 m^3/s with a generator shaft rotation of 888 Rpm, a turbine efficiency value of 37.0% at a water discharge of 0.0133 m^3/s. The Screw Turbine has a Torque of 0.60139072 Nm.